Manufacturing method of electrodeposit

By using multiple zirconium-based electrodes during the electrolyte purification process and adjusting their use termination time, the problem of zirconium-based electrode termination is solved, and the sustainability and production efficiency of electrolyte production are improved.

JP7661496B2Active Publication Date: 2025-04-14TOHO TITANIUM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023538292
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-30
Filing Date
2022-05-19
Publication Date
2025-04-14
Estimated Expiration
2042-05-19

AI Technical Summary

Technical Problem

During the electrolyte purification process, the electrodes of zirconium-based materials are difficult to continuously use because the decrease in zirconium content and the increase in oxygen content lead to an increase in resistance, which in turn affects the effective production of the electrolyte.

Method used

Multiple zirconium-based electrodes are used and the deposition time of the electrolyte on the cathode is extended by adjusting the use termination time of each electrode, thereby improving the sustainability of electrolyte production.

Benefits of technology

Extend the duration of electrolyte production, reduce the frequency of equipment downtime and restart, thereby improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661496000005
    Figure 0007661496000005
  • Figure 0007661496000006
    Figure 0007661496000006
  • Figure 0007661496000007
    Figure 0007661496000007
Patent Text Reader

Abstract

This method for producing an electrodeposit is a method for producing a Ti-containing electrodeposit by means of electrolytic purification using molten salt electrolysis, the method comprising an electrodeposit step in which an electrode 3 having a negative electrode 3b and a positive electrode 3a containing a crude titanium-based material containing Ti, Al, and O and having conductivity is used in a chloride bath as a molten salt bath Bm, and a purified titanium-based material is deposited on the negative electrode 3b to obtain an electrodeposit, wherein in the electrodeposit step, the electrode 3 has a plurality of positive electrodes 3a, and the use completion time of some positive electrodes 3a among the plurality of positive electrodes 3a is shifted to the use completion time of the remaining positive electrodes 3a so that a purified titanium-based material is deposited on the negative electrode 3b.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a Ti-containing electrodeposit by electrolytic refining using molten salt electrolysis. [Background technology]

[0002] Metallic titanium and titanium alloys are generally produced by the Kroll process, which is suitable for mass production. However, this process requires chlorination and reduction of titanium ore, and further requires crushing of sponge titanium lumps and production of metallic magnesium by electrolysis, and involves many steps, so it is difficult to say that metallic titanium and titanium alloys can be produced efficiently and at low cost.

[0003] In contrast, by electrolytic refining using molten salt electrolysis, titanium alloys can be easily produced.

[0004] As an example of this type of technology, Patent Document 1 describes a method for extracting a titanium product from titanium ore, the method comprising the steps of: mixing a chemical blend containing titanium ore and a reducing agent, the ratio of the titanium ore to the reducing agent being 0.9 to 2.4, the mass ratio of the titanium oxide component in the titanium ore to the reducing agent being equivalent to 0.9 to 2.4; heating the chemical blend to start an extraction reaction, the chemical blend being heated at a heating rate of 1°C to 50°C / min; heating the chemical blend at a reaction temperature of 1500 to 1800°C for a time between 5 minutes and 30 minutes; maintaining the titanium product at a temperature below 1670°C; cooling the chemical blend to a temperature below 1670°C; and separating the titanium product from the residual slag" includes the steps of "contains the titanium product in a reaction vessel having an anode, a cathode and an electrolyte; heating the reaction vessel to a temperature between 600°C and 900°C to form a molten mixture and applying an electrical differential between the anode and cathode to deposit titanium ions on the cathode; and terminating the electrical differential and cooling the molten mixture to form a refined titanium product, wherein the refined titanium product has a surface area of ​​at least 0.1 m 2 / g".

[0005] Furthermore, Patent Document 2 proposes a method for electrolytically refining titanium aluminide to produce a titanium master alloy, the method comprising the steps of: a. placing titanium aluminide containing more than 10 mass percent aluminum and at least 10 mass percent oxygen in a reaction vessel, the reaction vessel being designed with an anode, a cathode, and an electrolyte, the electrolyte containing a halogen salt of an alkali metal or an alkaline earth metal, or a combination thereof; b. heating the electrolyte to a temperature of 500° C.-900° C. sufficient to produce a molten electrolyte mixture; c. conducting an electric current from the anode through the molten electrolyte mixture to the cathode; and d. dissolving the titanium aluminide from the anode to deposit a titanium aluminum master alloy on the cathode. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2015-507696 [Patent Document 2] Special Publication No. 2020-507011 Summary of the Invention [Problem to be solved by the invention]

[0007] Specifically, electrolytic refining using molten salt electrolysis involves using a conductive crude titanium-based material containing Ti, Al, and O as an anode in a molten salt bath in an electrolytic cell, and applying a voltage between the anode and cathode. As a result, a refined titanium-based material with a higher purity than the crude titanium-based material is deposited on the cathode, and an electrodeposit can be obtained as the refined titanium-based material.

[0008] In such electrolytic refining, the Ti content of the anode decreases with use, and the O content increases relatively, causing high electrical resistance, making it difficult to continue using the anode. Therefore, in order to obtain a certain amount of refined titanium-based material, when the anode becomes unusable, it is necessary to stop operation in that electrolytic cell and build a new electrolytic cell to resume operation.

[0009] However, stopping and restarting the operation of the electrolytic cell requires many tasks, such as cleaning the used electrolytic cell, constructing a new electrolytic cell thereafter, drying the inside of the electrolytic cell in advance, forming a molten salt bath, etc., which leads to a decrease in the production efficiency of the electrodeposit. Therefore, it is desired to deposit a refined titanium-based material on the cathode over a long period of time in a single electrolytic refining process.

[0010] An object of the present invention is to provide a method for producing an electrodeposit which allows electrolytic deposition to be carried out over a relatively long period of time. [Means for solving the problem]

[0011] As a result of extensive research, the inventors have found that the molten salt bath can continue to be used for electrolytic deposition even after the anode containing Ti, Al, and O becomes unusable. Based on this knowledge, the inventors have conceived the idea that by using multiple anodes and shifting the end of use of some of them from the end of use of the rest, it would be possible to extend the electrolytic deposition of refined titanium-based materials onto the cathode.

[0012] The method for producing an electrodeposit of the present invention is a method for producing an electrodeposit containing Ti by electrolytic refining using molten salt electrolysis, and includes an electrodeposition step in which an electrode having an anode containing a crude titanium-based material containing Ti, Al and O and having electrical conductivity, and a cathode is used in a chloride bath as a molten salt bath, and a refined titanium-based material is deposited on the cathode to obtain an electrodeposit, in which the electrode has a plurality of anodes in the electrodeposition step, and the refined titanium-based material is deposited on the cathode by shifting the end of use of some of the plurality of anodes from the end of use of the remaining anodes.

[0013] In the electrodeposition step, the electrode may have a plurality of cathodes. In this case, in the electrodeposition step, the number of the anodes in the electrode is preferably greater than the number of the cathodes.

[0014] In the electrodeposition step, an electrode having a plurality of anodes arranged around the cathode can be used.

[0015] Preferably, the method includes an anode replacement step of replacing some of the anodes that have reached the end of their useful life and / or the remaining anodes with new anodes during the electrodeposition step.

[0016] In the electrodeposition step, it is preferable to carry out the anode exchange step while continuing the deposition of the purified titanium-based material on the cathode.

[0017] The electrodeposition step may be preceded by an extraction step of heating a mixture containing a titanium raw material containing titanium oxide, a reducing agent containing aluminum, and a separating agent, and extracting the crude titanium-based material from the mixture in a molten state.

[0018] The method for producing an electrodeposit of the present invention preferably includes a plurality of electrodeposition steps as the electrodeposition step, in which an anode containing, as a crude titanium-based material, the purified titanium-based material deposited on the cathode in the preceding electrodeposition step is used in the latter electrodeposition step, and in at least one electrodeposition step, the end of use of some of the anodes is shifted from the end of use of the remaining anodes. Effect of the Invention

[0019] According to the method for producing an electrodeposit of the present invention, the electrodeposition can be carried out for a relatively long period of time. [Brief description of the drawings]

[0020] [Figure 1] 1 is a cross-sectional view in the depth direction of a molten salt bath, showing an example of an electrolytic cell that can be used in a method for producing an electrodeposit according to an embodiment of the present invention. FIG. [Diagram 2]2 is a cross-sectional view taken along line II-II in FIG. 1, in a direction perpendicular to the depth direction of the molten salt bath. [Diagram 3] 11 is a cross-sectional view taken in a direction perpendicular to the depth direction, showing another example of the arrangement of electrodes in an electrolytic cell. FIG. [Figure 4] 11 is a cross-sectional view taken in a direction perpendicular to the depth direction, showing another example of the arrangement of electrodes in an electrolytic cell. FIG. [Diagram 5] 11 is a cross-sectional view taken in a direction perpendicular to the depth direction, showing another example of the arrangement of electrodes in an electrolytic cell. FIG. [Figure 6] 1 is a cross-sectional view taken in a direction perpendicular to the depth direction, showing the arrangement of electrodes in an electrolytic cell of Comparative Example 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described in detail. The method for producing an electrodeposit according to one embodiment of the present invention includes an electrodeposition step in which a voltage is applied between electrodes including an anode and a cathode immersed in a molten salt bath, and electrolytic deposition is performed on the cathode. The molten salt bath is a chloride bath. The anode includes a crude titanium-based material containing Ti, Al, and O (oxygen). This crude titanium-based material is conductive and can be subjected to electrolytic refining using molten salt electrolysis. In the electrodeposition step, a purified titanium-based material having a relatively high purity compared to the crude titanium-based material is deposited on the cathode. The purified titanium-based material has a lower content of at least one component other than Ti, such as Al or O, compared to the crude titanium-based material. Note that, before the electrodeposition step, an extraction step for obtaining the crude titanium-based material may be further included as an optional step that can be omitted. In addition, after the electrodeposition step, a removal step of the molten salt bath, such as washing and drying the purified titanium-based material and vacuum heating treatment of the purified titanium-based material, may be further included.

[0022] In this embodiment, an electrode having a plurality of anodes is used in the electrodeposition step. Then, the refined titanium-based material is deposited on the cathode so that the end of use of some of the anodes among the plurality of anodes does not coincide with the end of use of the remaining anodes but is shifted from the end of use of the remaining anodes. In this way, for example, when the use of either one of the anodes is ended, the other anode can still be used. As a result, the electrodeposition can be performed for a long period of time compared to the case where there is only one anode or the case where the end of use of the anodes is the same as that of the remaining anodes. Particularly preferably, an anode exchange step is performed during the electrodeposition step in which some anodes that have reached the end of use are replaced with new anodes.

[0023] The crude titanium-based material contains at least Ti, Al, and O. The refined titanium-based material contains at least Ti, and may further contain Al and / or O. The refined titanium-based material may be metallic titanium consisting of Ti and impurities, or a titanium alloy containing alloy elements with the remainder consisting of Ti and impurities.

[0024] (extraction process) In the extraction process, a mixture containing a titanium raw material containing titanium oxide such as titanium oxide (TiO2), a reducing agent containing aluminum (Al), and a separating agent is heated. It is assumed that the titanium oxide is reduced by the aluminum in the reducing agent based on the thermite reaction of, for example, 3TiO2+4Al→3Ti+2Al2O3. The heating temperature may be 1500°C to 1800°C. After the mixture is heated to a molten state, the crude titanium-based material and slag are separated due to the difference in density by the action of the separating agent, and the crude titanium-based material can be extracted.

[0025] The titanium raw material may be any material containing titanium oxide, and may be, for example, titanium ore that has been subjected to upgrading treatment such as leaching or other treatments as necessary. The content of TiO2 in the titanium ore used as the titanium raw material may be, for example, 50 mass% or more, typically 80 mass% or more, and particularly 90 mass% or more. The separating agent is used to facilitate separation of the crude titanium-based material from the slag after heating. Specifically, the separating agent is preferably one or more selected from calcium fluoride, aluminum fluoride, potassium fluoride, magnesium fluoride, calcium oxide, and sodium fluoride, and calcium fluoride (CaF2) is particularly suitable because it provides excellent separation of the crude titanium-based material from the mixture and has little effect on anything other than the separation. The reducing agent may be one that substantially contains aluminum (Al) alone, or may further contain Ca, Na, etc. For example, the mixture may be prepared by adjusting the molar ratio of TiO2:Al:CaF2 to 3:4 to 7:2 to 6.

[0026] The crude titanium-based material obtained in the extraction step contains Ti, Al, and O (oxygen), and may have, for example, a Ti content of 50% by mass to 80% by mass, an Al content of 5% by mass to 30% by mass, and an O content of 8% by mass to 30% by mass. The crude titanium-based material may have a Ti content of 50% by mass or more and 85% by mass or less, an Al content of 3% by mass or more and 40% by mass or less, and an O content of 0.2% by mass or more and 40% by mass or less. Typically, the crude titanium-based material may have a Ti content of 60% by mass or more, an Al content of 20% by mass or less, and an O content of 20% by mass or less.

[0027] Such crude titanium-based material has electrical conductivity and can be used in molten salt electrolysis by being included in the anode in the electrodeposition process described below. The resistivity of the crude titanium-based material is, for example, 1×10 -8 Ω m~1×10 -4 Ω m, typically 1×10 -7 Ω·m~5×10 -5 Ω m.

[0028] (electrodeposition process) In the electrodeposition step, various electrolytic cells can be used, but here, an explanation will be given using an electrolytic cell 1 shown in FIG. 1 as an example. The electrolytic cell 1 shown in the figure is configured to include a vessel-shaped or other vessel body 2 in which molten salt is stored to form a molten salt bath Bm, an electrode 3 having an anode 3a and a cathode 3b arranged so that at least a part of the electrode 3 is immersed in the molten salt bath Bm, and a power source (not shown) to which the electrode 3 is connected. Although not shown, the vessel body 2 may have an openable and closable lid member, and a gas passage for supplying an inert gas such as argon gas or discharging gas may be connected to the vessel body 2. The inside of the electrolytic cell 1 can be heated by a heater (not shown) arranged around the vessel body 2.

[0029] Here, the molten salt bath Bm is a chloride bath mainly containing metal chlorides, and may contain, for example, 70 mol% or more, further 80 mol% or more, or even 90 mol% or more of alkali metal chlorides and / or alkaline earth metal chlorides. Such chloride baths are preferred because they are less corrosive, have a lower environmental impact, and are less expensive than fluoride baths, bromide baths, and iodide baths. In particular, when a chloride bath containing magnesium chloride (MgCl2) is used, a purified titanium-based material can be obtained in which not only the O content but also the Al content is sufficiently reduced. The MgCl2 content in the chloride bath is preferably 30 mol% or more, further 50 mol% or more, further 80 mol% or more, further 85 mol% or more, and particularly 90 mol% or more. The chloride bath may contain one or more metal chlorides selected from lithium chloride (LiCl), sodium chloride (NaCl), potassium chloride (KCl), rubidium chloride (RbCl), cesium chloride (CsCl), beryllium chloride (BeCl2), calcium chloride (CaCl2), strontium chloride (SrCl2), and barium chloride (BaCl2), for example, at 70 mol% or less, further 50 mol% or less, further 20 mol% or less, further 10 mol% or less, and further 5 mol% or less.

[0030] In addition, the molten salt bath Bm may contain lower titanium chlorides having a lower Ti valence than titanium tetrachloride, specifically TiCl2 (titanium dichloride) or TiCl3 (titanium trichloride), if necessary. The content of titanium ions in the molten salt bath Bm is preferably 3 mol% or more, more preferably 5 mol% or more, even more preferably 6 mol% or more, particularly preferably 10 mol% or more, and may be 20 mol% or less. The content of metal chlorides and metal ions in the molten salt bath Bm can be measured by ICP emission spectrometry or atomic absorption spectrometry. The content of titanium ions is calculated as a percentage of the total content of metal ions in the molten salt bath Bm.

[0031] The anode 3a contains the crude titanium-based material obtained in the extraction step described above. As an example, the anode 3a has a cage-shaped container made of a metal such as Ni, Ni-based alloy, or Hastelloy, which has a smaller ionization tendency than Ti, and in this case, the crude titanium-based material in the form of particles or powder can be placed in the cage-shaped container. However, the shape of the anode 3a is not limited to this, and may be, for example, a rod-shaped, column-shaped, plate-shaped, or other arbitrary shape made from the crude titanium-based material by melting and casting. The cathode 3b can be made of Ti, and its shape is not particularly important and can be appropriately determined according to the shape of the anode 3a. The electrode 3 may further include a bipolar electrode placed between the anode 3a and the cathode 3b in addition to the anode 3a and the cathode 3b.

[0032] In the electrodeposition step, electricity is applied from a power source to the anode 3a and cathode 3b of the electrodes 3, and a voltage is applied between the electrodes 3. This causes titanium ions to dissolve from the crude titanium-based material contained in the anode 3a into the molten salt bath Bm, and the titanium ions are deposited as a refined titanium-based material on the cathode 3b. The refined titanium-based material deposited on the cathode 3b corresponds to the electrodeposit.

[0033] When the electrolytic deposition is performed in the electrodeposition step as described above, the electrical resistance of the anode 3a increases due to the gradual decrease in the Ti content of the crude titanium-based material in the anode 3a. As a result, the amount of the refined titanium-based material deposited on the cathode 3b per unit time decreases, or the refined titanium-based material does not deposit in a desired form on the cathode 3b, making it difficult to continue using the anode 3a. The end time of such use of the anode 3a can be determined based on the relationship between the current value flowing through the anode 3a and the theoretical amount of Ti elution. The theoretical amount of Ti elution can be calculated by calculating the amount of Ti elution at the anode 3a from the amount of electricity passed through the electrode 3, and then using the amount of Ti elution and the Ti content of the crude titanium-based material in the anode 3a before the start of current application, using the formula: theoretical amount of Ti elution = (amount of Ti elution calculated from the amount of electricity / Ti content of the crude titanium-based material) x 100. The amount of Ti elution is calculated from the amount of electricity using the formula: amount of Ti elution = amount of electricity ÷ valence of Ti ions in the molten salt bath ÷ Faraday constant × atomic weight of Ti. The valence of Ti ions in the molten salt bath, which is a chloride bath, is set to be divalent. For example, it is preferable to consider that the anode 3a has reached the end of its use when the theoretical amount of Ti elution reaches 50% or more, in terms of maintaining the production rate and the quality of the refined titanium-based material of the cathode. The end of use of the anode 3a is not limited to the above method, and may be appropriately determined based on the configuration of the electrode 3, etc.

[0034] In the past, when the anode 3a reached the end of its useful life, the operation of the electrolytic cell 1 was stopped, the electrolytic cell 1 was cleaned, and then the electrolytic cell 1 was reconstructed and the molten salt bath Bm was formed, and the operation was resumed. In particular, when the molten salt bath Bm contains MgCl2, since MgCl2 is hygroscopic, when the operation of the electrolytic cell 1 is resumed, it is necessary to heat the inside of the electrolytic cell 1 for a certain amount of time until the moisture is sufficiently removed before forming the molten salt bath Bm. In this way, stopping and restarting the operation of the electrolytic cell 1 every time the anode 3a becomes unusable increases the workload and reduces the production efficiency.

[0035] In contrast, in this embodiment, as illustrated in FIG. 1, a plurality of anodes 3a are provided, and the refined titanium-based material is deposited on the cathode 3b such that the end of use of some of the anodes 3a (e.g., one of the anodes 3a) is shifted from the end of use of the remaining anodes 3a (e.g., the other anode 3a).

[0036] As a result, even if some of the anodes 3a have reached the end of their useful life, the remaining anodes 3a have not yet reached the end of their useful life and are still in a usable condition. By continuing to use the remaining anodes 3a thereafter, the electrodeposition process can be carried out for a long period of time.

[0037] In order to shift the end of use of some of the anodes 3a from the end of use of the remaining anodes 3a, it is possible to shift the start of use (start of energization) between some of the anodes 3a and the remaining anodes 3a, or to make the content or composition of the crude titanium-based material contained in the anodes 3a different. In particular, shifting the start of use between some of the anodes 3a and the remaining anodes 3a makes it easier to control the difference in the end of use. For example, energization and use of the remaining anodes 3a can be started when 30% to 70% of the period of use from the start of use to the end of use of some of the anodes 3a has elapsed.

[0038] It is preferable that a plurality of cylindrical anodes 3a are arranged around a cylindrical cathode 3b, for example, as shown in FIG. 2. This makes it easier for titanium ions eluted from any of the anodes 3a to deposit as a purified titanium-based material on the cathode 3b located inside the anodes 3a in a cross section perpendicular to the depth direction of the molten salt bath. In FIG. 2, one cathode 3b is arranged at approximately the center of the line segment connecting the two anodes 3a in the cross section. In FIG. 3, four anodes 3a are arranged at equal intervals and apart from each other on a circumference centered on the cathode 3b in the cross section. It is preferable to arrange the anodes 3a and the cathodes 3b in this way so that the distance between each anode 3a and the cathode 3b is substantially equal.

[0039] When three or more anodes 3a are used, one or more but less than the total number of the anodes 3a among the anodes 3a are regarded as a part of the anodes 3a, and the remaining one or more but less than the total number of the anodes 3a are regarded as the remaining anodes 3a, so that the end of use of the part of the anodes 3a and the remaining anodes 3a can be made to differ from each other. In the example shown in FIG. 3, four anodes 3a are used, and one to three of them are regarded as a part of the anodes 3a, and the rest are regarded as the remaining anodes 3a. Note that when there are a plurality of remaining anodes, it is not necessary to treat them all in the same way, and the remaining anodes may be further divided into groups to manage the end of use times.

[0040] The electrode 3 may include a plurality of anodes 3a and a plurality of cathodes 3b. As shown in FIG. 4, a plurality of anodes 3a are arranged around each of a plurality of cathodes 3b. More specifically, in FIG. 4, four anodes 3a are arranged at equal intervals around each of three cathodes 3b, and two anodes 3a are shared between adjacent cathodes 3b. The example in FIG. 4 can be said to be arranged such that, in the cross section, one row and three columns of cathodes 3b are arranged between anodes 3a in two rows in one direction (vertical direction in FIG. 3) and four columns in an orthogonal direction (horizontal direction in FIG. 4), so as to be located at the center of the anodes 3a in the one direction and the orthogonal direction.

[0041] When the electrode 3 has a plurality of cathodes 3b, it is preferable that the number of anodes 3a is greater than the number of cathodes 3b. This makes it possible to reduce the frequency of the anode replacement step for the same amount of purified titanium-based material produced. However, the number of anodes 3a and cathodes 3b may be the same.

[0042] The shapes of the anodes 3a and the cathodes 3b are not limited to the columnar shapes such as the cylindrical shapes described above. In FIG. 5, a plurality of anodes 3a and a plurality of cathodes 3b, each of which is plate-shaped, are arranged alternately. Anodes 3a are located on both sides of the circumference of each cathode 3b. Even in this case, if the end of use of some of the anodes 3a and the remaining anodes 3a of the plurality of anodes 3a differs from that of the remaining anodes 3a, when the end of use of some or the remaining anodes 3a is reached, the deposition of the purified titanium-based material on the cathodes 3b can be continued by electrolysis between the anodes 3a and the cathodes 3b that can still be used. In the arrangement shown in FIG. 5, it is also possible to use the same number of anodes 3a and cathodes 3b.

[0043] The conditions for the electrodeposition step are, for example, the temperature of the molten salt bath Bm of 450°C to 900°C, and the current density at the cathode 3b of 0.01 A / cm 2 ~5A / cm 2 The current density is calculated using the formula: Current density (A / cm 2 ) = current (A) ÷ electrolytic area (cm 2 ) can be used to calculate the electrochemical potential. A current can be continuously applied to the electrodes 3, or a pulse current can be applied in which a current-on period and a current-off period are alternately repeated, with a current-off period during which the current value is set to zero. The maximum voltage between the electrodes 3 can be, for example, 0.2 to 3.5 V. During the electrodeposition step, the inside of the electrolytic cell 1 is preferably maintained in an inert atmosphere such as argon.

[0044] The purified titanium-based material deposited on the cathode 3b by electrolytic deposition can be recovered by physically peeling it off from the cathode 3b using a cutting tool or the like. The purified titanium-based material can be subjected to acid washing and / or water washing to remove the molten salt together with the cathode 3b on which it is electrodeposited, or after peeling it off from the cathode 3b. Thereafter, vacuum drying may be performed as necessary. In addition to the above-mentioned washing and drying, vacuum separation may be performed to remove the molten salt under high-temperature reduced pressure conditions. The more the number of electrodeposition steps is increased, the higher the titanium purity in the purified titanium-based material becomes, so the number of electrodeposition steps may be appropriately determined in consideration of the desired titanium purity. This allows the production of an electrodeposit of metallic titanium or a titanium alloy.

[0045] (Anode replacement process) It is preferable to replace some of the anodes 3a that have reached the end of their useful life during the electrodeposition process with new anodes 3a in an anode replacement process. By performing the anode replacement process, when the remaining anodes 3a reach the end of their useful life, it becomes possible to continue the electrodeposition with the new anodes 3a.

[0046] In addition, when some of the anodes 3a reach the end of their useful life, the remaining anodes 3a can still be used, so there is no need to temporarily stop electrolytic deposition during the anode exchange step. In other words, it is possible to carry out the anode exchange step while continuing deposition of the purified titanium-based material onto the cathodes 3b using the remaining anodes 3a in the electrodeposition step.

[0047] Furthermore, if some of the anodes 3a and the remaining anodes 3a are replaced with new anodes in an anode replacement process in sequence at the end of their life, the electrolytic deposition can be extended even further. In this case, since the end of life of some of the anodes 3a and the remaining anodes 3a differs from that of the remaining anodes 3a, the anode replacement processes for some of the anodes 3a and the remaining anodes 3a are also carried out at different times.

[0048] For example, in the arrangement shown in Fig. 3, among the four anodes 3a, in a cross section perpendicular to the depth direction of the molten salt bath, two anodes 3a located on both sides in one direction (the vertical direction in Fig. 3) separated by a cathode 3b can be set to end of use at the same time, and two anodes 3a located on both sides in a direction perpendicular to the one direction (the horizontal direction in Fig. 3) separated by a cathode 3b can be set to end of use at the same time. In this case, when either one of the two anodes 3a located on both sides in one direction or the two anodes 3a located on both sides in the perpendicular direction reaches the end of use, the two anodes 3a on that side can be replaced, and when the other two anodes 3a reach the end of use, the other two anodes 3a can be replaced.

[0049] Specifically, to replace the anode 3a, for example, the anode 3a (residue) that has been used is electrically disconnected from the power source, and the used anode 3a is removed from the electrolytic cell 1. Next, a new anode 3a is placed in the electrolytic cell 1 by immersing it in the molten salt bath Bm, and connected to the power source. Thereafter, when current is started to be passed through the new anode 3a, electrolytic deposition can be performed using the new anode 3a.

[0050] When the anode replacement process is performed, the value of the current flowing through each anode 3a may be checked periodically, for example, and the time to end use of each anode 3a and the necessity of replacement may be determined based on the current value. When the value of the current flowing through the anode 3a falls below a reference value, it may be determined that the anode 3a should be replaced.

[0051] When the anode replacement step is not performed, some of the anodes 3a that have reached the end of their useful life may be electrically disconnected from the power source and left as they are, or may be removed from the electrolytic cell 1.

[0052] (Multi-stage electrodeposition process) For further purification, the above-mentioned electrodeposition step can be performed in multiple stages. When performing multiple electrodeposition steps, the purified titanium-based material deposited on the cathode 3b in the previous electrodeposition step is used as the crude titanium-based material in the subsequent electrodeposition step. That is, in the subsequent electrodeposition step, the purified titanium-based material deposited on the cathode 3b in the previous electrodeposition step is used as the crude titanium-based material, and the anode 3a containing the crude titanium-based material is used. As a result, in the subsequent electrodeposition step, the purified titanium-based material from which impurities have been further removed is deposited on the cathode 3b. By performing multiple electrodeposition steps, it is also possible to produce an electrodeposit as metallic titanium that is almost free of impurities.

[0053] It is also possible to carry out multiple electrodeposition steps consecutively using the same electrolytic cell 1 and molten salt bath Bm. In this case, the polarity of the anode 3a and cathode 3b in the previous electrodeposition step is reversed, and the cathode 3b on which the purified titanium-based material is deposited can be used as the anode 3a in the subsequent electrodeposition step. In this case, a new cathode 3b is placed in the place where the anode 3a was placed in the previous electrodeposition step.

[0054] When a multi-stage electrodeposition process is performed, it is preferable to shift the end of use of some of the anodes 3a from the end of use of the remaining anodes 3a in at least one of the electrodeposition processes, as described above. In addition, the anode exchange process described above may be performed during the electrodeposition process. This makes it possible to extend the duration of the electrodeposition process.

[0055] (Electrodeposit) The electrodeposit as a purified titanium-based material obtained by one or more electrodeposition steps preferably has a total content of impurities other than Ti of 5000 ppm by mass or less, more preferably 3000 ppm by mass or less.

[0056] When the electrodeposit is metallic titanium, the one obtained in a single electrodeposition step may have an Al content of 800 ppm by mass to 0.4% by mass and an O content of 1000 ppm by mass to 2.0% by mass, for example. The one obtained in a multi-stage electrodeposition step may have an Al content of 5 ppm by mass to 1000 ppm by mass and an O content of 100 ppm by mass to 500 ppm by mass, with the remainder consisting of Ti and unavoidable impurities. The Al content and O content may be high due to the replacement of the anode in the electrodeposition step, the use of the same anode for long periods of time for electrodeposition, and the like, so the target values ​​of these contents may be appropriately determined in consideration of the operating conditions.

[0057] The inevitable impurities in the electrodeposit may be derived from the ore or the chloride bath. Specifically, the inevitable impurities in the electrodeposit may be 0.03 mass% or less of N (nitrogen), 0.01 mass% or less of C (carbon), 0.010 mass% or less of Fe, 0.05 mass% or less of Mg, 0.01 mass% or less of Ni, 0.03 mass% or less of Cr, 0.005 mass% or less of Si, 0.05 mass% or less of Mn, and 0.01 mass% or less of Sn.

[0058] The electrodeposit obtained as the refined titanium-based material has an almost granular appearance when observed with the naked eye, and may have a three-dimensional shape of linked polyhedral fine particles when observed under a microscope. When the electrodeposit is sieved through a sieve with 63 μm openings, the percentage of the particles remaining on the sieve may be, for example, 25% or more, or even 50% or more, and particularly 70% or more, by mass. Sieving is performed after the electrodeposit is crushed to a degree that does not cause it to break or shatter, in a glove box in an argon atmosphere with an oxygen concentration of 5% by volume or less. EXAMPLES

[0059] Next, a method for producing an electrodeposit according to the present invention was experimentally carried out and will be described below, however, the description here is merely for illustrative purposes and is not intended to be limiting.

[0060] A mixture containing titanium raw material containing TiO2, reducing agent Al, and separating agent CaF2 was heated to 1500℃ to 1800℃ under an argon atmosphere, and a crude titanium-based material containing Ti, Al, and O was extracted from the molten mixture. Titanium ore with a TiO2 content of 95% by mass was used. The mixture was adjusted to have a molar ratio of TiO2:Al:CaF2=3:4-7:2-6.

[0061] The components of the samples taken from the above-mentioned crude titanium-based material were analyzed by ICP emission spectrometry (PS3520UVDDII, manufactured by HITACHI Co., Ltd.) for metal components, inert gas fusion-infrared absorption method (TC-436AR, manufactured by LECO Co., Ltd.) for oxygen, inert gas fusion-thermal conductivity method (TC-436AR, manufactured by LECO Co., Ltd.) for nitrogen, and combustion-infrared absorption method (EMIA-920V2, manufactured by HORIBA, Ltd.) for carbon, and the impurity content of the crude titanium-based material was measured. The remainder other than the impurities is titanium. In addition, the resistivity of the samples taken from the crude titanium-based material in the form of a 10 mm square block was measured by a two-terminal measurement method (low resistance meter 3566-RY, manufactured by Tsuruga Electric Co., Ltd.). The results are shown in Tables 1 and 2.

[0062] [Table 1]

[0063] [Table 2]

[0064] The above crude titanium-based material was subjected to electrolytic refining using molten salt electrolysis. The electrolytic cell used had internal dimensions of 400 mm length and 800 mm width. Inside the electrolytic cell, a molten salt bath was prepared by dissolving only MgCl2, and had a depth of 400 mm. During electrolytic deposition, the temperature of the chloride bath was maintained at approximately 750°C, and the current density at the cathode was 0.4 A / cm 2 and the maximum voltage between adjacent anodes and cathodes was 1.8V.

[0065] In Examples 1, 2, and 4 and Comparative Example 1, the anode and cathode were used in the arrangements shown in Figures 1 and 2. In Example 3, plate-shaped anodes and cathodes were arranged as shown in Figure 5. In Comparative Example 2, a cylindrical anode was arranged to surround a columnar cathode as shown in Figure 6.

[0066] In all of Examples 1 to 4 and Comparative Examples 1 and 2, the anode had a Ni cage-shaped container having a large number of through holes into which the molten salt could penetrate, and the crude titanium-based material was placed in the cage-shaped container. In Examples 1, 2, and 4 and Comparative Example 1, the anode and the cathode were each cylindrical with a diameter of 100 mm and a height of 200 mm. The weight of the crude titanium-based material in the cage-shaped container in the anode in Examples 1, 2, and 4 and Comparative Example 1 was about 3.5 kg per cage-shaped container. In Example 3, the anode was flat with a length of 200 mm, a width of 200 mm, and a thickness of 40 mm, and the cathode was flat with a length of 200 mm, a width of 200 mm, and a thickness of 20 mm. The weight of the crude titanium-based material in the cage-shaped container in the anode in Example 3 was about 3.6 kg per cage-shaped container. In Comparative Example 2, the cathode was the same as in Examples 1, 2, and 4 and Comparative Example 1, and the anode was cylindrical with an outer diameter of 240 mm, an inner diameter of 200 mm, and a height of 200 mm. The weight of the crude titanium-based material in the cage-shaped container in the anode of Comparative Example 2 was about 6.2 kg.

[0067] In all of Examples 1 to 4 and Comparative Examples 1 and 2, the amount of electricity flowing through the anode was confirmed during electrolytic deposition of the purified titanium-based material onto the cathode, and the anode was determined to have reached the end of its useful life when the theoretical amount of Ti dissolved from the anode reached 50%.

[0068] In Examples 1 and 3, the start and end times of use of a plurality of anodes were shifted as shown in Table 3, and electrolytic deposition was terminated when all anodes had reached the end of use. In Example 3, the start and end times of use of the first and third anodes from the left in FIG. 5 were shifted from the second and fourth anodes from the left in FIG. 5. In Example 2, the anode that had reached the end of use was replaced once to continue electrolytic deposition, and the electrolytic deposition was terminated when the new anode after replacement reached the end of use. In Example 4, the anode that had reached the end of use was replaced twice to continue electrolytic deposition, and the electrolytic deposition was terminated when the new anode after replacement reached the end of use. In Example 2, a total of three anodes were used, and in Example 4, a total of four anodes were used.

[0069] In Comparative Example 1, the use of multiple anodes was started at the same time, and the anodes became unusable at the same time, and the electrolytic deposition was terminated. In Comparative Example 2, the electrolytic deposition was terminated when the use of the anodes was terminated.

[0070] The total electrodeposition time and the amount of electrodeposit per cathode for each of Examples 1 to 4 and Comparative Examples 1 and 2 are shown in Table 3. The Ti, Al, and O contents of the electrodeposits obtained in each of Examples 1 to 4 and Comparative Examples 1 and 2 are shown in Table 4.

[0071] [Table 3]

[0072] [Table 4]

[0073] As shown in Table 3, in Examples 1, 2, and 4 and Comparative Example 1, which had the same electrode arrangement, electrolytic refining could be performed while shifting the end time of the anode use. It can also be seen that when the anode was replaced, the total electrodeposition time was long and the amount of electrodeposition per cathode was large. As a result, a reduction in the workload associated with the suspension and restart of the operation of the electrolytic cell was also achieved.

[0074] In addition, electrolytic refining was performed in the same manner as in Example 3, except that the difference between the start and end times of use of the anode was set to zero hours (the start and end times of use of the anode were set to the same time). As a result, the total electrodeposition time was 10 minutes shorter than in Example 3. Therefore, the same effect was obtained even when the shape of the electrode was changed as in Example 3.

[0075] Furthermore, as shown in Table 4, the electrodeposits as purified titanium-based materials deposited on the cathodes in Examples 1 to 4 had impurities well reduced.

[0076] From the above, it has been found that the present invention enables electrolytic deposition over a relatively long period of time. [Explanation of symbols]

[0077] 1 electrolytic cell 2 Tank body 3 electrodes 3a anode 3b cathode Bm molten salt bath

Claims

1. A method for producing a Ti-containing electrodeposit by electrolytic refining using molten salt electrolysis, comprising the steps of: The method includes an electrodeposition step of obtaining an electrodeposit by using an electrode having an anode containing a crude titanium-based material containing Ti, Al, and O and having electrical conductivity, and a cathode, in a chloride bath as a molten salt bath, and depositing a refined titanium-based material on the cathode, a manufacturing method for an electrodeposit, wherein the electrode in the electrodeposition step has a plurality of anodes, and the end of use of some of the plurality of anodes is shifted from the end of use of the remaining anodes to deposit a purified titanium-based material on the cathode.

2. The method for producing an electrodeposit according to claim 1 , wherein in the electrodeposition step, the electrode has a plurality of cathodes.

3. The method for producing an electrodeposit according to claim 2 , wherein in the electrodeposition step, the number of the anodes in the electrode is greater than the number of the cathodes.

4. 4. The method for producing an electrodeposit according to claim 1, wherein an electrode in which a plurality of anodes are arranged around the cathode is used in the electrodeposition step.

5. The method for producing an electrodeposit according to any one of claims 1 to 3, further comprising an anode replacement step of replacing a part of the anodes that have reached the end of their use and / or a remaining anode with a new anode during the electrodeposition step.

6. 6. The method for producing an electrodeposit according to claim 5, wherein the anode exchange step is carried out while continuing deposition of the purified titanium-based material onto the cathode in the electrodeposition step.

7. The method for producing an electrodeposit according to any one of claims 1 to 3, further comprising, prior to the electrodeposition step, an extraction step of heating a mixture containing a titanium raw material containing a titanium oxide, a reducing agent containing an aluminum, and a separating agent, and extracting the crude titanium-based material from the mixture in a molten state.

8. The electrodeposition step includes a plurality of electrodeposition steps, and in a latter electrodeposition step, an anode containing the refined titanium-based material deposited on the cathode in the former electrodeposition step is used as a crude titanium-based material, 4. The method for producing an electrodeposit according to claim 1, wherein the end of use of some of the anodes is shifted from the end of use of the remaining anodes in at least one electrodeposition step.

9. A method for producing an electrodeposit described in any one of claims 1 to 3, wherein the crude titanium-based material has an Al content of 3 mass% or more.

10. A method for producing an electrodeposit described in any one of claims 1 to 3, wherein the crude titanium-based material has a Ti content of 85 mass% or less.

11. The method for producing an electrodeposit according to any one of claims 1 to 3, wherein the chloride bath contains magnesium chloride.

12. A method for producing an electrodeposit described in any one of claims 1 to 3, wherein the time to end use of the multiple anodes is determined based on the relationship between the current value flowing through the anodes or the amount of Ti elution.

Citation Information

Patent Citations

  • JP1974044919A

  • Method for refining ti

    JP1994173065A

  • Reduction method for metal oxide and reduction device for metal oxide

    JP2005105374A

  • Apparatus and method for titanium extraction and refining

    JP2015507696A

  • Device for conducting molten salt electrolysis and molten salt electrolysis method

    JP2018012861A